Epidemiological analysis of infection by the bovine viral diarrhea virus on family farms in Brazil - Marlos José Portela Rêgo; Antônio Fernando Barbosa Batista Filho; Pollyanne Raysa Fernandes de Oliveira; Jonas de Melo Borges; Carlos André Barbosa de França; Cláudia Pestana Ribeiro; Edviges Maristela Pituco; José Wilton Pinheiro Junior (Semina: Ciências Agrárias, 2016)
The aim of the present study was to determine the seroprevalence of infection by the bovine viral diarrhea virus (BVDV) on family farms, as well as to study the risk factors associated with the infection. In total, 319 blood serum samples were collected from cattle, of reproductive age (>24 months) in 24 herds from 11 cities of the brejo microregion in Pernambuco. The samples were subjected to the seroneutralization test to detect anti-BVDV antibodies. In order to identify the risk factors associated with the BVDV, a questionnaire epidemiologic was applied and followed by statistical analysis of logistic regression, with the serological test considered as the dependent variable (reagent or non-reagent). A prevalence of 51.1% (163/319; C.I. 45.5% - 56.7%) was found in the present study. Of the 24 herds sampled, 100.0% contained at least one reagent animal. The prevalence in the counties ranged from 23.1% to 70.0%. The following risk factors were identified in the present study: not providing colostrum (OR 3.85; p=0.018); disease unknown (OR 2.54; p=0.001) and consortium breeding (OR 1.76; p=0.013). Based on these results, it was clear that BVDV infection is widespread in herds on family farms in the microregion studied herein. Health education policies must be implemented for producers and professionals who provide technical assistance. In addition, based on the risk factors identified in the present study, hygiene-sanitary measures should be implemented in order to reduce the prevalence of the BVDV.